2016
DOI: 10.1038/srep32093
|View full text |Cite
|
Sign up to set email alerts
|

Cell non-autonomous regulation of hepatic IGF-1 and neonatal growth by Kinase Suppressor of Ras 2 (KSR2)

Abstract: Individuals with poor postnatal growth are at risk for cardiovascular and metabolic problems as adults. Here we show that disruption of the molecular scaffold Kinase Suppressor of Ras 2 (KSR2) causes selective inhibition of hepatic GH signaling in neonatal mice with impaired expression of IGF-1 and IGFBP3. ksr2−/− mice are normal size at birth but show a marked increase in FGF21 accompanied by reduced body mass, shortened body length, and reduced bone mineral density (BMD) and content (BMC) first evident durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 57 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…In contrast to the mild phenotype of ksr1 –/– mice, ksr2 –/– mice have reduced fertility and become spontaneously obese 56 59 . Pathways regulating adaptive thermogenesis, metabolic rate, and leptin-sensitive food consumption are implicated in KSR2-dependent energy balance 56 60 .…”
Section: Phenotypic Effects Of Ksr1/2 Genetic Inactivationmentioning
confidence: 87%
“…In contrast to the mild phenotype of ksr1 –/– mice, ksr2 –/– mice have reduced fertility and become spontaneously obese 56 59 . Pathways regulating adaptive thermogenesis, metabolic rate, and leptin-sensitive food consumption are implicated in KSR2-dependent energy balance 56 60 .…”
Section: Phenotypic Effects Of Ksr1/2 Genetic Inactivationmentioning
confidence: 87%
“…The low presence of Lrat and retinyl esters and enrichment of activated stellate markers suggests an altered basal state that may be more sensitive to these changes [14]. Postnatal increases in Igf1 expression [98] parallel the major increases in hepatocyte gene expression, including the 15 percent that depend on Cyp1b1 and retinol, which Pathways that convert acetate to cholesterol or oleoyl-CoA and retinaldehyde to RA or retinyl esters. All processes are inhibited in Cyp1b1-/-pups (KO) ( Table 1).…”
Section: Conclusion and Key Questionsmentioning
confidence: 99%
“…Ras-PI3K/AKT pathway was complex regulation progress which can regulate several downstream factors [21]. In order to investigate more about the underlying mechanism about how Ras pathway achieved their functions, we explored several downstream factors CYR61 [22], IGFBP3 [23], WNT16B [24], NT5E [25], GDF15 [26], CARD16 [27], which participated tumor cell growth and metastasis. Then, we observed that Ras G12V/Y40C pathway up-regulated the expression of CYR61 (p<.01), IGFBP3 (p<.01), WNT16B (p<.01) and decreased the expression of NT5E (p<.01), GDF15 (p<.001), GARD16 (p<.01, Figure 3(A)).…”
Section: H14 S35ph Participated In the Regulation Of The Downstream mentioning
confidence: 99%